Increased interleukin-10 associated with low IL-6 concentration correlated with greater survival rates in mice infected by rabies virus vaccinated against it and immunomodulated with P-acnes - Megid, Jane [UNESP]; Kaneno, Ramon [UNESP]; Nozaki, C. N.; Brito, CJC; Almeida, M. F. (Elsevier B.V., 2004)
Macrophage activity, cytokines serum concentration, serum neutralizing antibodies and lethality by rabies were evaluated in swiss mice experimentally infected with street rabies virus and submitted or not to antirabies vaccination and immunomodulation with P. acnes. Animals were killed at different times and serum was collected in order to evaluate cytokines concentration; peritonial and splenic macrophages were collected for macrophage activity evaluation. Greater survival rates higher IL-10 and low IL-6 serum concentration were observed in vaccinated animals treated using P. acnes. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: rabies; cytokines; immunomodulation; vaccine; macrophage; IL-10; IL-6